TANTANGAN PENDIDIKAN DALAM MENGHADAPI DEGRADASI KEPEDULIAN SOSIAL PESERTA DIDIK - Silvia Tabah Hati; Radhiah Amna; Syah Wardi (Prodi Tadris Ilmu Pengetahuan Sosial FITK UIN Sumatera Utara Medan, 2026)
The decline in social awareness among students is a critical manifestation of the moral crisis that threatens the quality of the nation's future generation. This phenomenon is not limited to individualistic behavior but is also reflected in actions such as bullying, lack of respect, and apathy toward the social environment. This article aims to critically analyze the fundamental challenges facing education, particularly in efforts to instill and foster social awareness values in students. Using a literature review method, this research synthesizes findings from various literatures to identify that the main challenges in education lie in the gap between cognitive understanding and practical application, the limited effectiveness of role models and habituation methods, and the lack of holistic synergy between the school, family, and community environments. This article concludes that to address the decline in social awareness, a reformulation of educational strategies is needed that focuses not only on knowledge transfer but also on internalizing values through a contextual approach, strengthening an inclusive religious culture, and wisely utilizing technology as a tool to build empathy and collective solidarity.